An Integrated Model for Small Farm Profitability: a case study - S. Regeena (Journal of Agricultural Extension Management, 2025)
Predominance of small holdings and the homestead farming system of agriculture distinguishes Kerala agriculture from the rest of the country. Homestead farming is a complex and innovative land use system prevalent in several tropical countries where limitation of size of holdings necessitates accommodation of a large number and variety of crops and enterprises in the same piece of land as a means of subsistence and as a source of cash income. They are mostly coconut based, low external input systems with a corresponding low output and consequent low income. The crop mix and cultivation practices are often guided by the farmer’s own perceptions and convenience rather than by any scientific recommendations.